Blood sampling and point of care testing: What competence do the nursing students achieve through their education? - Astrid-Mette Husøy; Kristine Lorgen; Turid Aarhus Braseth; Irene Nygård (Bioingeniøren, 2008)
Phlebotomy is a neglected and ignored area within the health services. Optimal blood sample procedure is essential for diagnosis and treatment. An ever increasing number of nurses are imposed the job of taking blood samples. The purpose of this project has been to gain knowledge about blood sampling procedures, practical training and point of care testing (POCT) received by nursing students and, in addition, their attitude to these activities. The goal was to uncover a possible need for a better training procedure.